Tradisi Uli, Pela dan Gandong pada Masyarakat Seram, Ambon, dan Uliase - J.Th.F. Pattiselano (Antropologi Indonesia, 1999)
In a traditionally Central Moluccan communities spread over the islands of Ambon, Haruka, Saparua, Nusalaut and in particular, Ceram, any conflict between two individuals of different denomination, or between two villages of different creeds, is usually settled in very short time. Conflicts do not spur intervillage riots as the Central Moluccan islanders have a strong commitment to their Pela and Gandong alliances and principles. However, the significance alliance systems had been undermined by the influx of migrants who have settled in the residential areas. The migrants have been totally excluded from the traditional pela system. With the decline influence of the traditional mechanism of authority, the outbreak of communal violence between the sa'lam (Moslem) and thesarane (Christian) inhabitants became unavoidable. The traditional laws have been ineffective as a problems-solving mechanism. The author maintains that it is high time to seriously consider the need to revive and maintain the alliance systems, and to adjust then to the present and future circumstances.